Índice de mecanización agrícola en el Ecuador - Lopez Lucas, Fabian Josue (2024)
Agricultural mechanization is a highly important factor in increasing productivity and food productivity efficiency at a global level. In the Ecuadorian Coast, agriculture is a primary factor in the economy and development, employing around 30% of the workforce and contributing 8 to 9% to the GDP, where mechanization has allowed productivity and profitability to increase. Ecuador has a percentage of 0.3kw/h, this problem arises from the dependence on manual labor and animal traction, which limits productivity. The objective of this document is to analyze the index of agricultural machinery in the Ecuadorian coast, since agricultural mechanization is the process of using advanced machinery and technology in agricultural operations to improve the efficiency and productivity of production. The modernization of the agricultural sector can contribute to economic growth by generating employment in activities related to the manufacturing, distribution and maintenance of machinery, as well as by increasing the production and export of agricultural products. Innovation in Ecuador's agricultural industry provides important opportunities for technological advancement. Creating more efficient agricultural machinery and equipment, adapted to local conditions, can have a significant impact on the country's agricultural production. Technology companies and research centers can focus on designing planters, harvesters, and tractors with advanced technologies, such as precision agriculture and GPS. Digitalization and precision agriculture allow for real-time monitoring of crops, optimization of resource use, and the promotion of more sustainable farming. To facilitate access to modern machinery, small and medium-sized farmers need to implement specific financial support programs.